1998
DOI: 10.1103/physrevb.57.5220
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-temperature phase diagram ofUPd2Si2and

Abstract: It is well established that the ternary intermetallic family of compounds UT 2 Si 2 , where T denotes a transition metal, shows a rich variety of electronic and magnetic ground-state properties. In order to better understand the magnetic properties of these materials, we have investigated the behavior of the electrical resistivity of UNi 2 Si 2 and UPd 2 Si 2 as a function of temperature and pressure. In the case of UNi 2 Si 2 , the proposed pressure-temperature phase diagram is very similar to its magnetic-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…We have found that applying σ along the [010] direction stabilizes the C-AF phase through tuning the competition between the C-and IC-AF orders. This tendency is clearly indicated by the increases of T Nl and q z under σ. Interestingly, the presently obtained σ − T phase diagram closely resembles the pressure p versus temperature phase diagram proposed by the resistivity measurements [10,11]. In general, it is expected that compressions using p and σ || [010] yield the different types of strain.…”
Section: Resultssupporting
confidence: 74%
“…We have found that applying σ along the [010] direction stabilizes the C-AF phase through tuning the competition between the C-and IC-AF orders. This tendency is clearly indicated by the increases of T Nl and q z under σ. Interestingly, the presently obtained σ − T phase diagram closely resembles the pressure p versus temperature phase diagram proposed by the resistivity measurements [10,11]. In general, it is expected that compressions using p and σ || [010] yield the different types of strain.…”
Section: Resultssupporting
confidence: 74%
“…Quirion et al determined the pressure-temperature phase diagrams for UNi 2 Si 2 and UPd 2 Si 2 by measuring the resistivity and compared these phase diagrams to predictions made using a mean-filed Landau-type analysis. 23 For UPd 2 Si 2 this analysis has reproduced qualitative features found in the experimental results. For UNi 2 Si 2 , however, this approach has been incompatible with the observed magnetic ground state.…”
Section: Discussionsupporting
confidence: 73%
“…The pressure-temperature phase diagram for UNi 2 Si 2 has been obtained. 21,23 It is similar to the magnetic-fieldtemperature phase diagram and it seems that the effect of the pressure is the same as that of the magnetic field in UNi 2 Si 2 . Quirion et al determined the pressure-temperature phase diagrams for UNi 2 Si 2 and UPd 2 Si 2 by measuring the resistivity and compared these phase diagrams to predictions made using a mean-filed Landau-type analysis.…”
Section: Discussionsupporting
confidence: 55%
“…2. Electrical resistivity studies of UNi 2 Si 2 exerted to an external hydrostatic pressure revealed that the value of T 1 (T 2 ) becomes strongly increased ͑weakly decreased͒, whereas T N seems to be pressure invariant. 5,6,9 As a result of pressure effects on T 1 and T 2 , the temperature range of the stability of AF-I is narrowing and vanishes above 3.2 GPa. 6 To discuss these phenomena from a thermodynamic point of view, highly accurate thermal expansion data of UNi 2 Si 2 at ambient pressure were strongly desired.…”
Section: Introductionmentioning
confidence: 99%